2017
DOI: 10.1128/jb.00213-17
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Mycoplasma hominis PG21 with Human Dendritic Cells: Interleukin-23-Inducing Mycoplasmal Lipoproteins and Inflammasome Activation of the Cell

Abstract: Mycoplasma hominis lacks a cell wall, and lipoproteins anchored to the extracellular side of the plasma membrane are in direct contact with the host components. A Triton X-114 extract of M. hominis enriched with lipoproteins was shown to stimulate the production of interleukin-23 (IL-23) by human dendritic cells (hDCs). The inflammasome activation of the host cell has never been reported upon M. hominis infection. We studied here the interaction between M. hominis PG21 and hDCs by analyzing both the inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…Recently, several studies have reported that mycoplasmas activate inflammasomes to induce IL‐1β production . We have also shown that M. salivarium and M. pneumoniae cells activate the NLRP3 inflammasome to produce IL‐1β in murine dendritic cells and macrophages .…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Recently, several studies have reported that mycoplasmas activate inflammasomes to induce IL‐1β production . We have also shown that M. salivarium and M. pneumoniae cells activate the NLRP3 inflammasome to produce IL‐1β in murine dendritic cells and macrophages .…”
Section: Introductionmentioning
confidence: 66%
“…Recently, several studies have reported that mycoplasmas activate inflammasomes to induce IL-1β production. [22][23][24][25][26][27] We have also shown that M. salivarium and M. pneumoniae cells activate the NLRP3 inflammasome to produce IL-1β in murine dendritic cells and macrophages. 28 However, the detailed mechanism of inflammasome activation triggered by mycoplasmas is not yet fully clarified.…”
mentioning
confidence: 83%
“…Two of the most well-studied TLRs are TLR2 and TLR6, both of which are pivotal in recognizing Mycoplasmal Macrophage-Activating Lipopeptide-2 (MALP-2), with the absence of either TLR leading to a lack of recognition and macrophage activation ( Takeuchi et al, 2002 ). Mycoplasmal lipoproteins can also activate myeloid cells through the inflammasome ( Chen et al, 2017 ; Goret et al, 2017 ). Amongst the Mycoplasma capable of activating inflammasome with their lipoproteins are M. salivarium and M. pneumoniae ( Shimizu, 2016 ; Sugiyama et al, 2016 ).…”
Section: Mechanisms Of Action Of Mycoplasmal Lipoproteinsmentioning
confidence: 99%
“…Mycoplasmal lipoproteins in M. hominis such as lipoprotein MHO_4720 were recently shown to induce production of Interleukin-23 (IL-23), by dendritic cells through activation of inflammasome ( Chen et al, 2017 ; Goret et al, 2017 ). Production of proinflammatory cytokines such as IL-23 has been shown to induce the expression of chemokines such as IL-17, allowing for effective containment of the infection ( Wu et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few MS proteins, including variable lipoprotein hemagglutinin (Narat et al, 1998;Lavric et al, 2007), cysteine protease (Cizelj et al, 2011), neuraminidase (Bercic et al, 2011), the putative nuclease MS53_0284 (Vasconcelos et al, 2005;Cizelj et al, 2016), and matrix metalloproteinase-2 (MMP-2) (Cizelj et al, 2016), have been identified as virulence determinants. In terms of host-pathogen interactions, Goret et al (2017) showed that M. hominis lipoproteins played a role in the activation of human dendritic cells and their immune responses. Addis et al (2011) utilized a proteomic approach to investigate the impact of M. agalactiae infection on mammary epithelium.…”
Section: Introductionmentioning
confidence: 99%